Aspirin Inhibition of In Vivo Effects of Intestinal Alkaline Phosphatase on Platelets - Iatridis, P. G; Iatridis, S. G; Ferguson, J. H (Thrombosis and Haemostasis, 1971)
Intravenous injections of 10 mg/kg purified intestinal alkaline phosphatase (AlPh) into (I) normal (non-aspirinized) rabbits and (II) aspirinized rabbits, show that aspirin inhibits significantly the AlPh effects on platelet aggregation and adhesion. Since aspirin does not change the assayable injected AlPh activity or its electrophoretic distribution, and whereas aspirin inhibits the platelet ADP release, it is very possible that the effects of AlPh on platelets are due to platelet ADP release by AlPh.Aspirin also inhibits the hypercoagulable effect of the injected AlPh. If aspirin acetylates the platelet membrane by its acetyl group, this could compete with HF (Hageman factor) which is a sialoglycoprotein, and could thus prevent the activation of HF on the surface of platelets.